The effects of grazing regimes on phenological stages, intervals and divergences of alpine plants on the Qinghai‐Tibetan Plateau. (27th February 2019) - Li, Yu; Dong, Shikui; Gao, Qingzhu; Zhang, Yong; Liu, Shiliang; Swift, David; Ganjurjav, Hasbagan; Hu, Guozheng; Wang, Xuexia; Yan, Yulong; Wu, Hongbao; Luo, Wenrong; et al.
Abstract: Questions: The impact of grazing on the phenology of alpine plants has not been deeply explored. In particular, how the phenology of all species in the alpine plant community is affected by grazing has seldom been monitored. Study Site: Qinghai‐Tibetan Plateau of China. Methods: A linear mixed model was used to explore the effect of grazing regimes (continuous grazing, grazing exclusion and rotational grazing), species, and individuals of species on phenological stages at the community level. One‐way ANOVA was used to examine the difference in phenological stage across different species under the same grazing regime and timing of the phenological stages of each species across different grazing regimes. Pearson correlation analysis was used to explore linkages between plant phenology and leaf traits, linkages between phenological stages, as well as their intervals across different species. Results: The green‐up and withering time of different species both exhibited various response patterns to grazing regimes. The flowering time of most species was delayed by grazing, whereas the fruiting time of most species remained stable across grazing regimes. There were significant linkages between phenological stages and leaf traits; for example fruiting time was negatively related to the ratio of leaf N content (LNC) to leaf P content (LPC) under all grazing regimes. The phenological stages themselves, and their intervals, showed close relations; for example fruiting time was positively related to withering time, and negatively related to its interval. The divergence was higher during the flowering time than during other phenological stages. The divergence of all phenological stages was highest under grazing exclusion. Conclusions: The shifts in flowering time were advantageous for these plants to adapt to grazing, as flowering time can regulate interspecific temporal patterns and maintain the stability of subsequent phenological stages. Among grazing regimes, grazing exclusion led to greatest divergence of phenological stages across species, which possibly creates potential reproductive gaps. Abstract : In the alpine meadows of the Qinghai‐Tibetan Plateau, the flowering time of most species was delayed by grazing, but the fruiting time of most species remained stable. Fruiting time was negatively related to the ratio of leaf N content to leaf P content. Grazing exclusion led to the greatest divergence of phenological stages across species, which possibly creates potential reproductive gaps.